2003
DOI: 10.1002/jso.10210
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative expression of protein markers of plasminogen activation system in prognosis of colorectal cancer

Abstract: uPA and uPAR may be independent predictors of liver metastasis, patient overall survival and cancer-specific survival after resection of colorectal tumors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
56
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 66 publications
(58 citation statements)
references
References 22 publications
2
56
0
Order By: Relevance
“…32 Activation of uPA is associated with a poor prognosis, distant metastasis, and local recurrence. 32 Protein expression of uPA is observed predominantly at the invasive tumor front and is correlated strongly with IHC expression of nuclear b-catenin, implicating uPA in Wnt pathway activation. 33 Moreover, the uPA gene appears to act as a direct target gene of b-catenin.…”
Section: Discussionmentioning
confidence: 99%
“…32 Activation of uPA is associated with a poor prognosis, distant metastasis, and local recurrence. 32 Protein expression of uPA is observed predominantly at the invasive tumor front and is correlated strongly with IHC expression of nuclear b-catenin, implicating uPA in Wnt pathway activation. 33 Moreover, the uPA gene appears to act as a direct target gene of b-catenin.…”
Section: Discussionmentioning
confidence: 99%
“…Bootstrap is a well-established computational statistic method to estimate the reliability of estimator. 23 It can be used to estimate the distribution of an estimator, e.g., the error rate of a classifier, based on N observed cases X 5 {X 1 , X 2 , . .…”
Section: Discussionmentioning
confidence: 99%
“…It is involved in localizing and promoting cell-surface plasminogen activation, plasmin formation and localized degradation of the extracellular matrix. 42 Overexpression of UPAR has been found in many cancers 23,[43][44][45][46] including pancreatic cancer, and contributes to tumor invasion and metastasis. 24,25 Recent studies by Ellis and colleagues have shown that pancreatic metastatic disease is dependent upon the UPA/ UPAR system, and that system activation and subsequent metastases is (i) mediated by insulin growth factor-1, hepatocyte growth (Table I).…”
Section: Discussionmentioning
confidence: 99%
“…11,12 In our previous work, we have reported the relationship between integrin atb6 and MMP-9 in colon cancer. We reported that atb6 expression in colon cancer cells lead to the increase in secretion of MMP-9 and that this secretion paralleled the level of cell-surface atb6 expression.…”
mentioning
confidence: 99%
“…10 Urokinase plasminogen activator (uPA )is found in cellular structures at the leading edge of migrating cells that are involved in adhesion, migration, invasion and intravasation and is considered to be a marker for malignancy in colon cancer. 11,12 In our previous work, we have reported the relationship between integrin atb6 and MMP-9 in colon cancer. We reported that atb6 expression in colon cancer cells lead to the increase in secretion of MMP-9 and that this secretion paralleled the level of cell-surface atb6 expression.…”
mentioning
confidence: 99%